Perception and Awareness of Tribal Parents towards Education of their Children’s - Irfan Ahmad Hakak; Asifa Ali (ILIN Institute Makassar, 2019)
The paper aimed to investigate the perception and awareness of tribal parents towards the education of their children’s in different tribal areas of district Anantnag. To achieve the objectives eight research questions were asked from respondents and the focus of the questions was existing perception, awareness and obstacles in path of education among tribal parents. Sample comprised of 200 tribal parents. The findings of the study disclosed that generally, tribal parents had soft corner for their daughter’s education. They are aware of significance of daughter’s education, but in some cases the education of girls were affected by migration and negligence of girls from co-education. The important thing in all scenarios is that people in tribal area of Anantnag district want to educate their daughters. The major problem for majority of them is the absence of schools or basic infrastructure within existing schools of the area.